2011
DOI: 10.1103/physreva.83.043401
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Feshbach resonances in near-threshold HOCOphotodetachment: A theoretical study

Abstract: The results of a theoretical study of HOCO − photodetachment are presented, with a view toward understanding the origin of two peaks observed by Lu and Continetti (Phys. Rev. Lett. 99, 113005 (2007)) in the photoelectron kinetic energy spectrum very close to threshold. It is shown that the peaks can be attributed to vibrational Feshbach resonances of dipole-bound trans-HOCO − , and not s-and p-wave shape resonances as previously assumed. Fixed-nuclei variational electron-HOCO scattering calculations are used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…A theoretical study by Miyabe et al found no shape resonances at these energies, and instead suggested that the resonance is a Feshbach resonance supported by dipole-bound anion states. 106 Their calculations predicted cisand trans-HOCO to have large dipole moments; 1.86 and 2.84 Debye, respectively, at the MP2 level of theory using Dunning's triple-z Gaussian-orbital basis set supplemented with diffuse primitive Gaussian functions. 106 In more recent experiments, the characteristic two-photon signal was also observed at 775 nm using the EIBT, and furthermore observed over a range of photon energies from 1.60 to 1.77 eV.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical study by Miyabe et al found no shape resonances at these energies, and instead suggested that the resonance is a Feshbach resonance supported by dipole-bound anion states. 106 Their calculations predicted cisand trans-HOCO to have large dipole moments; 1.86 and 2.84 Debye, respectively, at the MP2 level of theory using Dunning's triple-z Gaussian-orbital basis set supplemented with diffuse primitive Gaussian functions. 106 In more recent experiments, the characteristic two-photon signal was also observed at 775 nm using the EIBT, and furthermore observed over a range of photon energies from 1.60 to 1.77 eV.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…106 Their calculations predicted cisand trans-HOCO to have large dipole moments; 1.86 and 2.84 Debye, respectively, at the MP2 level of theory using Dunning's triple-z Gaussian-orbital basis set supplemented with diffuse primitive Gaussian functions. 106 In more recent experiments, the characteristic two-photon signal was also observed at 775 nm using the EIBT, and furthermore observed over a range of photon energies from 1.60 to 1.77 eV. This confirms that the resonance(s) responsible for this effect must be broad, consistent with a dense manifold of dipole-bound states.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…Photoelectron spectra near threshold (772 nm) revealed two peaks at low electron kinetic energy that were not conclusively assigned, as a broad background arising from internally excited anions prevented unambiguous resolution of the peaks . These features were recently suggested to arise from vibrational Feshbach resonances in dipole-bound states, though the potential for pure photodetachment was not ruled out …”
mentioning
confidence: 99%
“…The transition dipole moments obtained from the Kohn trial function have been shown to be variationally stable [23] and the method has been applied in past studies on the photoionization of diatomic molecules such as H 2 and CO [24,25]. The Kohn technique was also used to calculate the radiative electron attachment to the CN radical [13] and to study the photodetachment of HOCO − [26].…”
Section: Theoretical Approach To Photodetachmentmentioning
confidence: 99%